Impact of Primary Tumor Size, SUVmax of Primary Tumor and the Most Avid Neck Node on Baseline 18FDG PET/CT upon Disease Recurrence in Head and Neck Oropharyngeal SCC Using Standardized Imaging Protocol - Nosheen Fatima; Areeba Zaman; Unaiza Zaman; Sidra Zaman; Rabia Tahseen; Maseeh Uz Zaman (World Journal of Nuclear Medicine)
Objective The purpose fo this prospective study was to find the impact of primary tumor size (Ts), standardized uptake values (SUVmax) of primary tumor, and the most avid neck node on disease recurrence in patients with head and neck oropharyngeal squamous cell carcinoma (HNOP-SCC). Material and methods We included patients with HNOP-SCC (without distant metastasis—M0 disease) who had pre- and post-treatment F-18 fluorodeoxyglucose positron emission tomography/computed tomography (18FDG PET/CT) using strict standardized imaging protocol from 2017 to 2019. Based on follow-up (18FDG PET/CT) findings, patients were categorized as disease free (no or minimal 18FDG uptake ≤ background over surgical bed and no distant metastasis) and disease recurrence (18FDG uptake > background over surgical bed with or without nodal and/or distant metastasis). Ts and SUVmax of primary tumor and the most avid neck node were compared and impact of these was studied upon disease recurrence. Results Total 112 patients were included. No significant difference was seen in mean age (overall: 60 ± 14 years), gender distribution (overall M:F: 69:31%), body mass index (overall: 25.20 ± 5.82), and history of diabetes (overall: 19%) between disease-free and disease recurrence groups. Similarly, no significant difference was observed for fasting blood sugar (overall: 110 ± 28 mg%), 18FDG dose (overall: 169 ± 37 MBq), and uptake period (overall: 70 ± 12 minutes) between two groups ensuring strict adherence to standardized imaging protocol. Significant difference (p < 0.05) was observed between disease-free and disease recurrence for Ts (25 ± 10 vs. 33 ± 14 mm), SUVmax of primary tumor (6.2 ± 6.8 vs. 9.3 ± 7.2) and the most avid neck node (2.1 ± 3.3 vs. 4.7 ± 5.9) and median follow-up (13 ± 12 vs. 08 ± 13 months), respectively. Using receiver operating characteristic analysis, Ts greater than 29 mm, baseline tumor SUVmax greater than 4.6, and nodal SUVmax greater than 6.2 were found independent predictors for disease recurrence. Nodal SUVmax greater than 6.2 was found an independent predictor of shortest disease-free survival (DFS) than Ts and tumor SUVmax. Conclusion We conclude that in HNOP-SCC, primary Ts (> 29 mm), SUVmax of primary tumor (> 4.6), and the most avid neck node (> 6.2) in baseline 18FDG PET/CT using standardized imaging protocol are the independent predictors of disease recurrence. Furthermore, SUVmax greater than 6.2 of the most avid node predicts the shortest DFS than primary Ts and SUVmax of primary tumor.